Thermally assisted hydrolysis and derivatisation techniques for the characterisation of organic materials - Challinor, John M. (Curtin University, 1998)
This thesis describes the development of a novel method for the rapid identification of complex organic materials, including macromolecules, that involves a high temperature simultaneous hydrolysis and derivatisation reaction. In this procedure, aqueous quaternary alkylammonium hydroxides are made to react with a wide range of complex molecular species, including synthetic and natural polymers, under high temperature flash heating conditions. The hydrolysis products are converted to derivatives, such as alkyl esters or alkyl ethers. The reaction forms the basis for a modified pyrolysis gas chromatography (Py-GC) identification technique. Although the process is primarily intended for the rapid identification of polymers which are susceptible to hydrolysis, it is also valuable for characterisation of a variety of hydrolysable lower molecular weight species, such as polymer additives, triglycerides and natural waxes.The reaction takes place when an intimate mixture of an aqueous quaternary alkylammonium hydroxide solution is flash heated with the analyte in a conventional pyrolysis unit, and "on-line" GC-MS is used to separate and identify the reaction products. Analytes included synthetic polyester resins and phenolic polymers, natural products such as lipids and wood extractives, and natural polymers including lignocellulose, proteins and kerogen.Reaction variables, such as temperature, pH analyte particle size, substrate, and the derivatising reagent were studied, in order to find the optimum conditions for the reaction. While the reaction occurs at temperatures as low as 358 degrees celsius, a 770 degrees celsius reaction temperature was adopted to allow direct comparison with Py-GC data. A high pH of the derivatising reagent was found to be necessary to achieve an efficient hydrolysis of the macromolecule. Small particle size gives better conversion to derivatised products. The nature of the heating substrate did not appear to influence the reaction. Tetraalkylammonium hydroxides (TAAH) were found to be the most effective derivatising reagents for the reaction. Tetramethylammonium hydroxide (TMAH) was the most useful derivatising reagent, since the methyl derivatives of the hydrolysed products were conveniently chromatographed and usually had well known mass spectra. Other TA-AHs were useful for (i) producing higher molecular weight alkyl derivatives of low molecular weight side chains in some polymers, e.g., acetate groups in polyvinyl acetate, (ii) the purpose of determining sites of pre-existing methylation in natural products such as lignocellulose, or (iii) cases where methylation products could be confused with existing pyrolysis products.The reaction mechanism is believed to involve hydrolysis of the organic material, formation of the tetra-alkylammonium salt, and thermal degradation of the quaternary ammonium salt to alkylated derivatives. Some evidence is presented to support this mechanism, which is considered to be ionic in character, rather than a free radical reaction.A detailed study of the reaction of alkyd resins indicated that polyhydric alcohols, polybasic acids, degree of cure, oil length, and rosin acid and epoxy modification could be determined. The reaction of rosin modified phenolic resins (tert-butyl phenol formaldehyde and para-nonyl phenol formaldehyde), gave rosin acid methyl esters and easily identifiable products from the synthetic components.Fatty acid methyl esters could be obtained directly from lipids, such as vegetable oils, without time consuming preparative steps. The problems of base catalysed isomerisation of the double bonds in polyunsaturated fatty acids were overcome by reducing the amount of base used for the reaction. The reaction facilitated the identification of fatty acids in woolwax, the triglycerides in cosmetic products, and lipids in trace quantities of human fingerprint deposits.A more reliable representation of the chemical structure of lignocellulose in softwood and hardwood species was obtained by the reaction, as compared to conventional PyGC which underestimates the aromatic carboxylic acid moieties. Gymnosperm or angiosperm origin was indicated by the presence of solely guaiacyl, or both guaiacyl and syringyl derived groups, respectively. Other extraneous extractable material was identified simultaneously, including aliphatic and aromatic acids, which would not normally be detected by conventional Py-GC.An alternative method involved extracting the wood with TMAH, followed by pyrolysis of the extract, to give less complex but more specific GC profiles. The TMAH extraction procedure also indicated some characteristic biomarker species as well as guaiacyl and syringyl derived compounds. The pyrolysis of tetraethylammonium hydroxide (TEAH) extracts revealed the sites of pre-existing methylation in the Eucalyptus marginata species.The thermally assisted hydrolysis and alkylation method which has been developed is usually superior to the conventional Py-GC procedure for those polymers which are prone to hydrolysis, since it results in products which are more readily related to the polymer structure. For example, concerted hydrolysis and alkylation of polyester resins results in alkyl carboxylate esters and the alkyl ethers, whereas in conventional Py-GC the products are alkenes and carboxylic acids. Carboxylic acids are more difficult to chromatograph by GC, and aromatic carboxylic acids in particular are susceptible to decarboxylation under the pyrolysis conditions.The reaction procedure has provided an alternative approach to the characterisation of submicrogram quantities of a range of synthetic polymers, natural products and natural polymers, which has not previously been possible without lengthy chemical degradation procedures. Although it has not displaced the conventional Py-GC technique, it has given a new dimension to the characterisation of organic materials, providing a powerful tool for forensic science investigations and the analysis of complex materials.